Evidence of rutile-to-anatase photo-induced electron transfer in mixed-phase TiO2 by solid-state NMR spectroscopy1. Issue 72 (18th September 2015) - Sun, Xiaoming; Dai, Weili; Wu, Guangjun; Li, Landong; Guan, Naijia; Hunger, Michael
<x xml:space="preserve">Abstract</x> The evidence of rutile-to-anatase photo-induced electron transfer in mixed-phase TiO2 is obtained using solid-state NMR spectroscopy with ethanol as a probe molecule.